Spatial Distributions of Auroral Zone X-Rays as Viewed from Rocket Altitudes - Kodama, Masahiro; Oguti, Takasi (1976)
P(論文) A single-stage sounding rocket S-210JA-3 was launched to an altitude of 130 km over Syowa Station, Antarctica, on 22 July 1971, for high time resolution image formings of spatial patterns of auroral X-rays. A pair of NaI (T1) scintillation counters, sensitive to X-ray energies of 4 KeV to 40 KeV, was used at mounting angles of 45° and 135° with the rocket axis. They succeeded in scanning a considerable part of the sky through the composite operation of the spinning and coning motions of the rocket, and recorded X-ray fluxes with a magnitude of the order of 10 times the background X-ray flux. As a result, a sequence of iso-photo maps, taken every 5 seconds, of X-ray fluxes with respect to the azimuthal and elevation angle coordinates was achieved covering different altitudes between 73 km and 131 km. The forty-four maps thus obtained during the entire flight of 225 seconds demonstrate the fine structures in spatial patterns, and in particular the existence of several points of origin of auroral X-rays and their temporal changes. It will be shown that the gross spatial character of X-rays is well correlated with those of visual aurora seen from the ground and of ultraviolet emissions measured from on board the same rocket. However, detailed comparisons of X-rays with ultraviolet emissions reveal that none of the fine structures of X-ray distributions were detected by means of the ultraviolet detector. The altitude dependence of the X-ray flux will be discussed taking into account temporal and spatial variations of the auroral luminosity. departmental bulletin paper